A Semiotic Approach to Qatari Political Discourse: The Speech of Emir Tamim Bin Hamad as a Case Study - Alshammari, Houda Maazi (Journal of Cultural Analysis and Social Change, 2025)
This study examines the political discourse of Emir Tamim bin Hamad Al Thani from a semiotic perspective, aiming to analyze the linguistic and visual signs and symbols he employs to convey his political and humanitarian message. Focusing on the Emir’s speech delivered at the United Nations General Assembly on September 25, 2024, within the context of the Gaza conflict, the research investigates how semiotic elements were utilized to reinforce his Arab and humanitarian stance and to advocate for justice, human rights, and the rule of law. Adopting a semiotic methodology that integrates linguistic, visual, temporal, and spatial analysis, the study draws on the theoretical frameworks of Saussure, Peirce, Greimas, and Roland Barthes. The findings reveal that the Emir’s political discourse strategically employs repetition, symbolism, metaphor, metonymy, and various rhetorical devices to establish effective communication with an international audience, emphasize human values, and enhance Qatar’s image as both a political and humanitarian actor on the global stage. The study further concludes that the dynamic interaction between language, signs, symbols, space, and time contributes to the production of a coherent and influential political discourse capable of shaping public opinion and guiding ethical and political positions.